Indonesian biogas market: an opportunity alongside B100 program - Rianawati, Elisabeth; Sagala, Saut; Dwiputra, Andreas; Anhorn, Johannes; Hilbert, Jorge Antonio; Rosslee, Dwight; Mohammed, Mutala; Salie, Yaseen; Colmorgen, Felix; Decorte, Mieke; Stummer, Benhard; Zacepins, Aleksejs; et al. (Etaflorence, 2025)
With the continued growth of the palm oil industry in Indonesia, the Government of Indonesia has been triggered to set up the national targets for new and renewable energy through biodiesel blend mandatory (B100 program). As more solid and liquid wastes will be generated as a result of biodiesel production, it can be convertered to renewable energy using biogas plants. Along with the B100 program, the POME-based biogas development seems could be more notable. However, the biogas technology market in Indonesia is still in a nascent state. This study aims to attempt the macro-environmental factors analysis of the Indonesian biogas industry using PESTEL analysis. With the existence of cross-sectional stakeholders, overlapping, and conflicting interests whose policies and actions may cause obstacles that influence the industry, this paper aims to capture the macro picture of the biogas maket and identify its challenges alongside de B100 program. It is concluded that barriers for deployment of biogas come term of wage, environment, and risks for indigenous people, lack of experts and success case to prove new technology implementation, and weak and inconsistency of the law enforcement.